2021
DOI: 10.1016/j.ress.2021.107551
|View full text |Cite
|
Sign up to set email alerts
|

Deep reinforcement learning driven inspection and maintenance planning under incomplete information and constraints

Abstract: Determination of inspection and maintenance policies for minimizing long-term risks and costs in deteriorating engineering environments constitutes a complex optimization problem. Major computational challenges include the (i) curse of dimensionality, due to exponential scaling of state/action set cardinalities with the number of components; (ii) curse of history, related to exponentially growing decision-trees with the number of decisionsteps; (iii) presence of state uncertainties, induced by inherent environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 68 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…Recently, studies have proposed deep reinforcement learning (DRL) for adaptive maintenance planning [32], where no fixed thresholds are needed to schedule maintenance. In [36], DRL is used to schedule the replacement of a component whose degradation is represented by 4 discrete states. In [37], the maintenance of multi-component systems is optimised using DRL, where they assume that the degradation follows a compound Poisson process and a Gamma process.…”
Section: Relevant Studies On Maintenance Planningmentioning
confidence: 99%
“…Recently, studies have proposed deep reinforcement learning (DRL) for adaptive maintenance planning [32], where no fixed thresholds are needed to schedule maintenance. In [36], DRL is used to schedule the replacement of a component whose degradation is represented by 4 discrete states. In [37], the maintenance of multi-component systems is optimised using DRL, where they assume that the degradation follows a compound Poisson process and a Gamma process.…”
Section: Relevant Studies On Maintenance Planningmentioning
confidence: 99%
“…To overcome this curse of dimensionality, further research efforts are suggested towards the integration of the FAD criterion with POMDP-based deep reinforcement learning (DRL) approaches. The capability of POMDP-based DRL approaches to efficiently provide optimal I&M strategies for large state space problems has been demonstrated in Andriotis and Papakonstantinou (2021).…”
Section: Discussionmentioning
confidence: 99%
“…The deep reinforcement learning algorithm is seen as the most promising method. It has been used for multiple engineering applications such as inspection and maintenance planning [20,21], satellite communications [22], and production systems [23]. Although many studies have demonstrated its ability in tackling the optimization problems with high dimensional decision space and state space [24][25][26][27], few studies have used it for the emergency management, such as the decisions in the recovery process [28].…”
Section: Fig 1 Illustration Of the Concept Of Resilience And Maintena...mentioning
confidence: 99%